Supporting Everyday Activities through Always-Available Mobile Computing - Saponas, Scott (University of Washington, Department of Computer Science and Engineering, 2010)
Ubiquitous Computing provides us a vision of computing fading into the background and gracefully supporting our everyday activities. However, our interactions with mobile devices still demand so much of our physical, visual, and cognitive attention that mobile applications are tasks unto themselves, often interrupting the activities they seek to support. For example, the physical interfaces of portable music players are well designed for situations where people can see the controls while holding the device in their hand. However, when people use these devices to listen to music or manage their workout while exercising, they often are forced to interrupt their activity just to advance to the next song. As our primary use of computing continues to move off the desktop, we need new interfaces to mobile computing that expand the types of situations in which people can make use of computing. In this dissertation, I explore always-available interfaces to improve our current interactions and to enable new mobile computing opportunities.